2007
DOI: 10.1590/s0074-02762007000800001
|View full text |Cite
|
Sign up to set email alerts
|

Association of insecticide use and alteration on Aedes aegypti susceptibility status

Abstract: Dengue and dengue hemorrhagic fever, vector-borne diseases transmitted by the mosquito

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 13 publications
(12 reference statements)
2
46
0
10
Order By: Relevance
“…Temephos resistance was even found in Cuiabá in contrast to an earlier report from that locality (Campos & Andrade 2003), suggesting recent local resistance dissemination (MS/SVS 2007). High temephos RR values were found at localities from Northeast and Southeast Brazil, corroborating previous data , Macoris et al 2007, Montella et al 2007). Strikingly, the Henrique jorge population exhibited very high RR levels, although these assays were performed with specimens reared in the laboratory for three generations without insecticides.…”
Section: Discussionsupporting
confidence: 91%
“…Temephos resistance was even found in Cuiabá in contrast to an earlier report from that locality (Campos & Andrade 2003), suggesting recent local resistance dissemination (MS/SVS 2007). High temephos RR values were found at localities from Northeast and Southeast Brazil, corroborating previous data , Macoris et al 2007, Montella et al 2007). Strikingly, the Henrique jorge population exhibited very high RR levels, although these assays were performed with specimens reared in the laboratory for three generations without insecticides.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated successive increases in resistance to pyrethroid insecticides over time in dengue vectors, often following repeated applications of this insecticide class for dengue control (9,29,30). Furthermore, a cagebioassay in the Caribbean island of La Martinique demonstrated that the efficacy of deltamethrin applied by a vehicle thermal fogger was compromised by resistance in the local Ae.…”
Section: Impact Of Current Levels Of Insecticide Resistance On Vectormentioning
confidence: 99%
“…Since there is no vaccine currently available for dengue and DHF prevention, the eradication of the mosquito adults and larvae, which is primarily relied on applications of synthetic insecticides or larvicides, is the most commonly adopted strategy for reducing morbidity (WHO, 2008). According to the literature, the organophosphate temephos is one of the most employed commercial insecticides for the control of this vector (Macoris et al, 2007;Garcez et al, 2009;Oliveira et al, 2010). However, these chemicals can affect non target population and may increase mosquito resistance to insecticides.…”
Section: Resultsmentioning
confidence: 99%